2016
DOI: 10.1007/s11682-016-9535-4
|View full text |Cite
|
Sign up to set email alerts
|

Non redundant functional brain connectivity in schizophrenia

Abstract: Schizophrenia is considered a disorder of abnormal brain connectivity. Although whole brain maps of averaged bivariate voxel correlations have been successfully applied to study connectivity abnormalities in schizophrenia these maps do not adequately explore the multivariate nature of brain connectivity. Here we adapt a novel method for highdimensional regression (supervised principal component regression) to estimate brain maps of multivariate non redundant connectivity (NRC) from resting functional Magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…A meta-analysis [27] also reported increased ALFF in the medial superior frontal gyri, which is consistent with our study. Furthermore, previous studies have reported decreased ALFF in the bilateral lingual [28], calcarine, cuneus, and postcentral gyri [44] areas of the brains of SZ patients (Table 3).…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis [27] also reported increased ALFF in the medial superior frontal gyri, which is consistent with our study. Furthermore, previous studies have reported decreased ALFF in the bilateral lingual [28], calcarine, cuneus, and postcentral gyri [44] areas of the brains of SZ patients (Table 3).…”
Section: Discussionmentioning
confidence: 87%
“…67,68 In the end, 24 studies reporting 28 data sets that investigated ALFF differences between patients with schizophrenia and healthy controls were eligible for inclusion. [14][15][16][17][18]21,23,[25][26][27][28][69][70][71][72][73][74][75][76][77][78][79][80] Of these, 11 (13 data sets) were first-episode samples 14,15,18,21,23,25,26,69,71,76,81 and 13 (15 data sets) were chronic samples. 16,17,27,28,70,[72][73][74][75][77][78][79][80] Of the first-episode samples, 69% were medication-naïve; the results for medication-naïve patients with first-episode sc...…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
“…MRI acquisitions included a T1 structural image, a resting-state fMRI sequence, and an fMRI acquisition obtained during performance of the n back task (a working memory task). Acquisition parameters as well as a detailed description of the preprocessing steps applied to the images can be found in previous reports: T1 (Salvador et al, 2017b), resting-state fMRI (Salvador et al, 2017a), and the n -back task (Fuentes-Claramonte et al, 2019). Images from all modalities were coregistered to the same standard MNI152 T1 2 mm template.…”
Section: Methodsmentioning
confidence: 99%